Nebulized Heparin With N-Acetylcysteine and Albuterol Reduces Duration of Mechanical Ventilation in Patients With Inhalation Injury. (April 2019) - McGinn, Kaitlin A.; Weigartz, Katie; Lintner, Alicia; Scalese, Michael J.; Kahn, Steven A.
Objective: Nebulized heparin has been proposed to improve pulmonary function in patients with inhalation injuries. The purpose of this study was to evaluate the impact of nebulized heparin with N -acetylcysteine (NAC) and albuterol on the duration of mechanical ventilation in burn patients. Methods: This is a retrospective study evaluating mechanically ventilated adult patients admitted to a regional burn center with inhalation injury. Outcomes were compared between patients who were prescribed a combination of nebulized heparin with NAC and albuterol versus similar patients who did not. Results: A total of 48 patients met inclusion criteria (heparin n = 22; nonheparin n = 26). Patients in the nonheparin group had higher percentage of total body surface area (TBSA) burned (29.00 [5.75-51.88] vs 5.25 [0.50-13.25] %TBSA; P = .009), longer duration of mechanical ventilation (6.50 [2.75-17.00] vs 3.00 [1.00-8.25] days; P = .022), and longer intensive care unit length of stay (LOS) (3.00 [3.00-28.75] vs 5.50 days [2.00-11.25]; P = .033). Upon regression, use of heparin was the only variable associated with reducing the duration of mechanical ventilation ( P = .039). Conclusion: Nebulized heparin in combination with NAC and albuterol was associated with a significant reduction in the duration of mechanical ventilation.